2021
DOI: 10.18332/tid/136040
|View full text |Cite
|
Sign up to set email alerts
|

Perceived health risks associated with the use of tobacco and nicotine products during the COVID-19 pandemic

Abstract: Perceptions of health risks and harms are associated with tobacco product experimentation, initiation, frequency, and intensity of use, as well as quit attempts [1][2][3] . In tobacco regulatory science, findings of health risk misperceptions that can promote harmful tobacco use behaviors are used to prompt and inform corrective action through new public education efforts or new requirements relating to product characteristics (e.g. flavors or appearance), product packaging, and labeling design, advertising an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Nevertheless, the perceived risk of having COVID-19 when smoking LCCs was low in our sample. This finding builds upon previous research that reported cigar smokers, including LCC users, tend to underestimate its health risks compared to cigarettes [ 22 , 39 , 40 ]. Moreover, perceived COVID-19 risk may be related to how LCCs are smoked.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, the perceived risk of having COVID-19 when smoking LCCs was low in our sample. This finding builds upon previous research that reported cigar smokers, including LCC users, tend to underestimate its health risks compared to cigarettes [ 22 , 39 , 40 ]. Moreover, perceived COVID-19 risk may be related to how LCCs are smoked.…”
Section: Discussionsupporting
confidence: 85%
“…To our knowledge, no studies have investigated how perceptions about COVID-19 risks affect CAI and CAB use. Concurring with the literature that suggests perceived health risk of smoking is a strong predictor of smoking cessation status or quit attempts [ 19 , 20 , 21 ], a few studies showed that a higher perceived risk of COVID-19 is related to a higher likelihood of decreasing tobacco use [ 8 , 11 , 22 ], but those findings were not specific to LCCs.…”
Section: Introductionmentioning
confidence: 99%
“… 45 , 47 , 52 , 77 , 86 , 87 Such perceived risk of infection or disease severity, or concern over lung health more generally, was associated with reduced tobacco use. 49 , 79 , 80 , 86 , 88 , 89 , 90 , 91 , 92 Additional reasons for reduced tobacco use included wanting to help others who might have COVID-19; 88 concerns that parents might learn about their use; 49 and closure of bars and pubs, suspension of classes, and reduced socialising with friends. 52 Those with chronic illness were also more likely to reduce tobacco use during the pandemic.…”
Section: Tobacco Product Use Behaviours During the Pandemicmentioning
confidence: 99%
“…Studies suggest that stress-related coping increases in cigarette smoking occurred among some smokers, whereas fears of COVID-19 health risks may have been associated with some individuals' decisions to reduce use of or quit tobacco products. [3][4][5][6][7] A 2022 analysis 8 of nationally representative crosssectional data from the Behavioral Risk Factor Surveillance System (BRFSS) survey reported a decrease in smoking prevalence during the COVID-19 pandemic but did not assess changes in smoking cessation behaviors. To address these gaps, we used 2 distinct but complementary data sources to investigate changes in past-year quit attempts, recent successful cessation, and sales of nicotine replacement therapies (NRTs; effective cessation treatments used by 25% of US smokers in quit attempts 1,9 ) before and during the COVID-19 pandemic in the US.…”
Section: Introductionmentioning
confidence: 99%